University Education in Additive Manufacturing and the Need to Boost Design Aspects - Borgianni, Yuri; Maccioni, Lorenzo; Russo Spena, Pasquale; Shunmugavel, Manikanda Kumar (Proceedings of the International Design Society, 2019)
Additive Manufacturing (AM) is a potentially revolutionary technique in industry with claims of high skills shortage in the recent days. It is assumed that full exploitation of AM capabilities can be made possible by a paradigm shift steered by engineering design. Future generations of engineers might benefit from Design for Additive Manufacturing (DfAM), which targets AM potential and enables design freedoms. In this context, the paper investigates AM education for a better understanding of the main AM-related subjects taught in universities. To this scope, the authors gathered 52 syllabi of courses taught in highly-ranked technical universities worldwide that relate to AM. From the investigation, it emerges that AM is the core discipline of the course in 42 out of 52 cases and considered widely as an independent domain to date. As for taught subjects, it was found that design aspects in AM and DfAM are poorly focused on, while manufacturing and process areas are the most popular. This poses a challenge especially to the design community, as the current situation might limit the exploitation of AM capabilities.